Impact of international laboratory partnerships on the performance of HIV/sexually transmitted infection testing in five resource-constrained countries. - Gaydos, C A; Rizzo-Price, P A; Balakrishnan, P; Mateta, P; Leon, S R; Verevochkin, S; Yin, Y P; Quinn, T C; Strader, L C; Pequegnat, W (International journal of STD & AIDS, 2011)
To review a quality control and quality assurance (QC/QA) model established to ensure the validity and reliability of collection, storage and analysis of biological outcome data, and to promote good laboratory practices (GLPs) and sustained operational improvements in international clinical laboratories, we conducted a two-arm randomized community-level HIV behavioural intervention trial in five countries: China, India, Peru, Russia and Zimbabwe. The trial was based on diffusion theory utilizing a Community Popular Opinion Leaders (CPOLs) intervention model with behavioural and biological outcomes. The QC/QA model was established by the Biological Outcome Workgroup, which collaborated with the Data Coordinating Center and John Hopkins University Reference Laboratory. Five international laboratories conducted chlamydia/gonorrhoea polymerase chain reaction (PRC)-based assays, herpes simplex virus type 2 enzyme immunoassay (EIA), syphilis serology (rapid plasma regain and Treponema pallidum particle agglutination assay, HIV serology (EIA/Western blot) and Trichomonas vaginalis culture. Data were collected at baseline, 12 and 24 months. Laboratory performance and infrastructure improved throughout the trial. Recommendations for improvement were consistently followed. Quality laboratories in resource-poor settings can be established, operating standards can be improved and certification can be obtained with consistent training, monitoring and technical support. Building collaborative partnership relations can establish a sustainable network for clinical trials, and can lead to accreditation and international laboratory development.
Keywords: Adolescent; Adult; Behavior Therapy; Clinical Laboratory Techniques; Developing Countries; Female; Humans; International Cooperation; Male; Middle Aged; Quality Control; Sexually Transmitted Diseases; Young Adult